Efficacy and safety of Traditional Chinese Medicine in alleviating symptoms associated with myocardial bridge: a systematic review and meta-analysis - Ren, Jiaqi; Feng, Teng; Wu, Xize; Wu, Qiuying; Huang, Yuxi; Li, Yue; Yu, Kaifeng; Gong, Lihong (Frontiers in Pharmacology, 2025)
BackgroundWith the advancement of technology, the detection rate of myocardial bridge (MB) has gradually increased and attracted attention. However, management options for symptomatic MB are limited, and Traditional Chinese Medicine (TCM) has emerged as a potential complementary approach for managing symptoms in MB patients. This study conducted a meta-analysis by pooling data from clinical randomized controlled trials (RCTs) to assess the efficacy and safety of TCM in alleviating symptoms in patients with MB.MethodsRCTs of TCM for MB were searched in PubMed, Embase, Web of Science, Cochrane Library, CBM, Wanfang, VIP, and CNKI databases from their inception to 1 April 2025. Patients diagnosed with MB via angiography were included in the study. The intervention group received either TCM alone (TCM-alone) or TCM combined with biomedicine (TCM + BM), while the control group received conventional biomedicine alone. Two investigators independently screened the literature according to the inclusion and exclusion criteria. The risk of bias in the included studies was assessed using Stata/MP 18.0 software. A meta-analysis was then conducted using RevMan 5.4.1 software to evaluate outcomes such as angina efficacy, electrocardiogram efficacy, TCM syndrome score efficacy, and the Seattle Angina Scale (SAQ). Subgroup analysis was performed according to the treatment regimen and duration of the intervention group.ResultsA total of 18 publications were included, containing 1,224 participants, with 613 in the intervention group and 611 in the control group. Meta-analysis results showed that TCM significantly improved angina efficacy [RR = 1.30, 95% CI (1.21, 1.40), P < 0.00001], reduced angina attack frequency [MD = −0.96 episodes per week, 95% CI (−1.32, −0.59), P < 0.00001], improved electrocardiogram efficacy [RR = 1.31, 95% CI (1.20, 1.42), P < 0.00001], enhanced TCM syndrome scores [RR = 1.45, 95% CI (1.28, 1.64), P < 0.00001], and reduced physical limitation [MD = 5.95, 95% CI (2.25, 9.64), P = 0.002], angina stability [MD = 12.10, 95% CI (7.37, 16.83), P < 0.00001], angina frequency [MD = 11.29, 95% CI (6.93, 15.64), P < 0.00001], treatment satisfaction [MD = 23.44, 95% CI (19.26, 27.61), P < 0.00001], and disease perception [MD = 10.69, 95% CI (5.66, 15.72), P < 0.0001] scores in the SAQ, as well as Self-rating Anxiety Scale (SAS) [MD = −12.83, 95% CI (−13.95, −11.71), P < 0.00001] and Self-rating Depression Scale (SDS) [MD = −6.97, 95% CI (−8.41, −5.52), P < 0.00001] scores, and did not increase adverse reactions [RR = 0.82, 95% CI (0.51, 1.34), P = 0.43]. Subgroup analysis results indicated that, compared with the control group, both the TCM-alone [RR = 1.22, 95% CI (1.11, 1.34), P < 0.0001] and TCM + BM [RR = 1.38, 95% CI (1.24, 1.55), P < 0.00001] groups improved angina efficacy; the TCM + BM group improved ECG efficacy [RR = 1.26, 95% CI (1.16, 1.37), P < 0.00001] and TCM syndrome scores [RR = 1.54, 95% CI (1.30, 1.81), P < 0.00001], while the TCM-alone group did not improve ECG efficacy [RR = 1.53, 95% CI (0.92, 2.53), P = 0.10] or TCM syndrome scores [RR = 1.16, 95% CI (0.97, 1.40), P = 0.11]. Salvia miltiorrhiza Bunge [Lamiaceae; Salviae miltiorrhizae radix et rhizoma] and Ligusticum chuanxiong Hort. [Apiaceae; Chuanxiong rhizoma] are high-frequency medicinal substances for MB symptom management.ConclusionTCM combined with biomedicine significantly improves angina symptoms, reduces attack frequency, enhances electrocardiographic parameters, alleviates TCM syndrome scores, and improves quality of life in patients with myocardial bridge, with a favorable safety profile. Crucially, TCM monotherapy showed no significant benefits for objective ischemia markers (ECG) or TCM syndrome scores, underscoring its role as a complementary adjunct rather than an alternative to standard care. However, these findings should be interpreted with caution due to the limited number of included RCTs, poor quality, small sample size, and single-center studies. Future large-scale, high-quality RCTs are warranted to confirm these results and further evaluate the efficacy and safety of TCM for symptom management in MB.Systematic Review Registrationidentifier CRD420251000868.